why tantheta into cottheta =1
Answers
Answered by
0
Step-by-step explanation:
By definition cot(θ)=1tan(θ). Explanation: tan(θ)⋅cot(θ). XXXX =tan(θ)⋅1 tan(θ). XXXX =tan(θ) ⋅1tan(θ). XXXX =
Answered by
0
Answer:
plz refer to the attachment
hope this helps u
:-)❤
Attachments:
![](https://hi-static.z-dn.net/files/da3/d17a010a3582c3379d2ce3b5ff41360b.jpg)
Similar questions
Social Sciences,
6 months ago
English,
6 months ago
Science,
6 months ago
Math,
1 year ago
English,
1 year ago
India Languages,
1 year ago
India Languages,
1 year ago